2020
DOI: 10.2139/ssrn.3613232
|View full text |Cite
|
Sign up to set email alerts
|

Dying to Divulge: The Determinants of, and Relationship Between, Desired and Actual Disclosure

Abstract: for their invaluable comments on earlier versions of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…While much of the literature on privacy tends to focus on the risks of information leakage, those concerned about privacy need to contend with the fact that in most situations privacy-related motivations are counterpoised against potentially even stronger motives for socializing, connecting, and sharing information. Individuals have many reasons for sharing information, including economic benefits that result from strategic revelation or withholding, and an array of psychological motives (Carbone & Loewenstein, 2020). One study using subjective measures as well as fMRI (Tamir & Mitchell, 2012) found that information sharing is inherently pleasurable, particularly when the information relates to one's own thoughts and feelings.…”
Section: The Drive To Sharementioning
confidence: 99%
“…While much of the literature on privacy tends to focus on the risks of information leakage, those concerned about privacy need to contend with the fact that in most situations privacy-related motivations are counterpoised against potentially even stronger motives for socializing, connecting, and sharing information. Individuals have many reasons for sharing information, including economic benefits that result from strategic revelation or withholding, and an array of psychological motives (Carbone & Loewenstein, 2020). One study using subjective measures as well as fMRI (Tamir & Mitchell, 2012) found that information sharing is inherently pleasurable, particularly when the information relates to one's own thoughts and feelings.…”
Section: The Drive To Sharementioning
confidence: 99%
“…Our own unpublished work takes such investigation a step further by attempting to document experiences of a visceral desire to disclose and quantify this experience (Carbone & Loewenstein, 2020). Asked whether they had ever felt like they were “dying” to tell someone something, the overwhelming majority (79%) of study participants ( N = 215) indicated that they had indeed experienced such an intense desire to disclose in the past.…”
Section: The Drive To Disclosementioning
confidence: 99%
“…Although the desire to disclose was correlated with a binary indicator of whether the information was ultimately disclosed or not, average ratings varied dramatically across "scenarios," ranging from À0.79 (for the mean desire to share a painful childhood memory) to 3.63 (for the mean desire to share an infuriating customer service experience). One-quarter of respondents (25%) indicated that they experienced an "intense, overwhelming desire to share (=5)" in at least one of the scenarios presented to them, and another quarter (26%) provided at least one rating of 4 or 5 on the desire to share scale, suggesting that the experience of a powerful desire to disclose is indeed commonplace (above analysis not presented in Carbone & Loewenstein, 2020).…”
Section: Impulsivitymentioning
confidence: 99%
“…a) Privacy Motivation: Individuals are motivated to share information online by various goals, such as economic benefits [30], psychological benefits and social benefits [12]. While the effects of those disclosure decisions (e.g., lower price, psychological pleasure, and social engagements) are typically immediate or in a relatively short term, possible information leakage or privacy risks are typically delayed or occur in the future.…”
Section: Human Factors In the Privacy Of Cavsmentioning
confidence: 99%